2006
DOI: 10.2478/s11756-006-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-and long-term effects of cadmium on transmembrane electric potential (E m) in maize roots

Abstract: In this study, the effects of Cd on root growth, respiration, and transmembrane electric potential (Em) of the outer cortical cells in maize roots treated with various Cd concentrations (from 1 µM to 1 mM) for several hours to one week were studied. The Em values of root cells ranged between −120 and −140 mV and after addition of Cd they were depolarized immediately. The depolarization was concentration-dependent reaching the value of diffusion potential (ED) when the Cd concentration exceeded 100 µM. The valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
5
15
1
Order By: Relevance
“…The effect of Cd and Pb on the E m of Nitellopsis obtusa cells observed here Table 1. may be caused by both the decrease of the PM H + -ATPase activity and the changes in plasma membrane permeability, especially for Ca 2+ and K + ions (Morse and Spanswick 1984;Małkowski et al 2005;Karcz and Kurtyka 2007). This suggestion is supported by our previous study (Małkowski et al 2005), in which we showed that the Cd ions at high concentration (1.0 mM) decreased the content of Ca 2+ in root cells of Zea mays L., and also by other authors who showed that Cd, but not Pb, induced a depolarization of the membrane potential (Llamas et al 2000;Pavlovkin et al 2006;Karcz and Kurtyka 2007) which resulted from decreased PM H + -ATPase activity Gonsalvez 1987, 1989;Burzyński and Buczek 1994;Fodor et al 1995;Astolfi et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…The effect of Cd and Pb on the E m of Nitellopsis obtusa cells observed here Table 1. may be caused by both the decrease of the PM H + -ATPase activity and the changes in plasma membrane permeability, especially for Ca 2+ and K + ions (Morse and Spanswick 1984;Małkowski et al 2005;Karcz and Kurtyka 2007). This suggestion is supported by our previous study (Małkowski et al 2005), in which we showed that the Cd ions at high concentration (1.0 mM) decreased the content of Ca 2+ in root cells of Zea mays L., and also by other authors who showed that Cd, but not Pb, induced a depolarization of the membrane potential (Llamas et al 2000;Pavlovkin et al 2006;Karcz and Kurtyka 2007) which resulted from decreased PM H + -ATPase activity Gonsalvez 1987, 1989;Burzyński and Buczek 1994;Fodor et al 1995;Astolfi et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Alterations of the PM-H-ATPase activity can be assessed by studying changes in the E M . According to our results, the effect of Ni on E M of grapevine adventitious root epidermal cells differed from that reported for the other divalent cation, cadmium (Llamas et al 2000, Pavlovkin et al 2006, Fiala et al 2015 and mercury (Repka et al 2013). In shortterm experiments, Ni induced rapid and concentration-dependent transient depolarization of the PM in the grapevine roots indicating its entry into the cells.…”
Section: Discussioncontrasting
confidence: 53%
“…One of these studies described that after adding of 100 µM Cd the mean E M value measured in DF zone in the interval of 10-20 h did not differ from that obtained in control cells in rice and barley roots [30]. On the contrary, an other study demonstrated that Cd elicited depolarization in maize cortical cells in the MZ [9,27].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, alterations of the membrane permeability (increasing efflux rates) or of E M , and hence a decrease of ion influx rates, may explain the metal effects on lowered nutrient uptake. There are several reports on the effect of Cd and Ni on these parameters, but they have been studied separately and in different plants [2,22,23,27,30]. These metals, in short term experiments, depolarized cell membranes and it has been suggested that this effect could be involved in metal toxicity.…”
Section: Acta Biologica Hungarica 66 2015mentioning
confidence: 99%
See 1 more Smart Citation